Infrastructure and logistics for economic activity of states - M. Derkach, Ella (2020)
The article reveals that each of the world's leading countries aims to develop economic ties with the world's leading countries through transport. It aims to create transport and logistics centers and the development of transport and logistics systems. The main opinions of scientists on the processes of development of transport and logistics centers in the country are considered. It is emphasized that logistics centers promote the development of a new direction of transportation. It is about intermodal transportation Through close cooperation between transport companies that are part of the logistics center provide an opportunity to plan an international transportation scheme in order to optimize the use of certain types of transport resources and vehicles.